Niche differentiation in microorganisms capable of using alternative reduced nitrogen sources studied across depth and between oxic and anoxic ocean regions - Huanca-Valenzuela, Paulina; Cram, Jacob A.; Fuchsman, Clara A. (Frontiers in Marine Science, 2024)
Introduction Assimilation of reduced nitrogen is less energetically costly than assimilation of oxidized forms. In the open ocean, ammonium is generally absent from the water column, including in oxygen-deficient zones (ODZs). Some microorganisms can use alternative organic reduced nitrogen forms like urea and cyanate, as indicated by the presence of cyanase (cynS) and urease (ureC) genes. Methods Here we examine the Hawaii Ocean Time series, two stations in the Eastern Tropical South Pacific ODZ and one in the Eastern Tropical North Pacific ODZ, using phylogenetic read placement of metagenomic reads to define the proportion of each taxon capable of using cyanate and/or urea in oxic and anoxic environments. Results An improved phylogenetic tree found that Thioglobaceae and Verrucomicrobia had the capability to use urea. Our detailed examination of all the microbial groups able to use cyanate and urea illuminated that niche differentiation, an adaptation to minimize competition, determines chosen nitrogen sources, partitioning by depth and oxygen. Urease genes were found in Picocyanobacteria and SAR11 in surface waters, Thaumarchaeota and Nitrospina in deep waters, Thioglobaceae and Cand. Scalindua in ODZs, and Verrucomicrobia in the deep oxycline. In the ODZs, the percentage of Anammox bacteria that contained cynS was double that of those containing ureC, and their cynS transcripts were abundant, indicating a preference for cyanate over urea. Discussion While Prochlorococcus could utilize cyanate in the deep chlorophyll maximum, in the ODZs, Prochlorococcus uses nitrite rather than compete with Cand. Scalindua for cyanate, even though cyanate is present. SAR11 and Prochlorococcus may compete for urea in surface waters, but for SAR11, the presence of ureC was negatively correlated with nitrate concentration (p = 10−17), with ~ 40% of SAR11 genomes containing the ureC gene in oxic surface waters but none at depth, indicating that SAR11 bacteria switched to using nitrate when available. In the oxycline above the ODZ, where Thaumarchaeota and Nitrospina both could use urea, 50% of Nitrospina were also able to use cyanate, and their cyanase transcripts were present. This use of dissolved organic N should allow a higher biomass of N-cycling microbes and higher N-transformation rates than in a system competing for ammonia only.